Problems of improving physical training at this stage of the transformation of the system of physical education - Ажиппо, Александр Юрьевич; Артемьева, Галина Павловна; Бурень, Нина Владимировна; Дорофеева, Татьяна Ивановна; Друзь, Валерий Анатольевич; Жерновникова, Яна Викторовна; Нечитайло, Мария Валерьевна; Новицкая, Наталья Анатольевна; Пугач, Ярославна Игоревна (Slobozhanskyi Herald of Science and Sport, 2016)
Aghyppo O., Artemyeva G., Buren N., Dorofeeva T., Druz V., Zhernovnikova Ya., Nechytailo M., Novitskaya N., Puhach Ya. Purpose: building a system of recreational physical culture on the basis of taking into account the individual characteristics of physical development and physical condition of the local population. Material & Methods: analytical review of the scientific literature on the issue of the research; use the results of previous studies carried out in KSAFC in this area and published in «Slobozhanskyi science and sport bulletin» during 2015 year; the use methods of similarity and analogy, also signs semantic spaces. Results: insolubility of the problem individual approach in organizing recreational physical culture in the previous period explained lack of representation of the content of individual of norm in the assessment of physical development and methods of comparison measure the differences being compared multicomponent objects. In held scientific research were developed signs semantic spaces with the introducted in its a single measure of comparable signs it possible to establish the qualitative structure of objects to be compared with any number of comparable parameters. Obtained methods separation of equifinality results into its component quality components. It is possible to obtain methods of estimating the biological age with the establishment of the individual characteristics of its course; divide the physical condition of its component parts; obtain methods for determining the available physical preparedness depending on the characteristics of the flow of biological age and current physical condition. Conclusions: оbtained results of the research make it possible to proceed to the development of monitoring physical development, physical preparedness and physical condition of the various population groups and on this basis to create a scientifically based of system improving physical training on the basis of which to develop a complex of "ready to work and defense of the fatherland".